2007
DOI: 10.1177/230949900701500305
|View full text |Cite
|
Sign up to set email alerts
|

Proximal Femoral Nail for Treatment of Trochanteric Femoral Fractures

Abstract: Purpose. To report outcomes of 87 consecutive patients treated with a proximal femoral nail (PFN) for trochanteric femoral fractures. Methods. 17 men and 70 women aged 58 to 95 (mean, 85) years with trochanteric femoral fractures underwent PFN fixation using an intramedullary nail, a lag screw, and a hip pin. Fractures were classified according to the AO system; the most common fracture type was A2 (n=45), followed by A1 (n=36) and A3 (n=6). The position of the lag screw within the femoral head was measured. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 20 publications
(23 reference statements)
3
40
0
4
Order By: Relevance
“…In one of our patients though the fracture had united, we could see the 'Z effect' with the migration of hip pins into the joint in which case the nail was explanted. The complication rates in our study were comparable with the other studies [13][14][15] . (figure 7) Incomplete reduction 4 -------# at distal lock 2 -------Fixed in distraction 2 1 -----1 Incorrect neck screw 2 1 -----1 Implant cutout --4 4 ---1 Delayed union --1 -2 --3 AVN / NU ---1 -2 -2 Difficult distal lock ---4 4 --4 Fixed in varus ----3 -2 3 Screw backout ----1 5 2 2 Metin Uzun et al [16] , in 2009, In a study of 35 patients reported Long-term radiographic complications following treatment of unstable intertrochanteric femoral fractures with the proximal femoral nail and effects on functional results.…”
Section: Discussionsupporting
confidence: 82%
“…In one of our patients though the fracture had united, we could see the 'Z effect' with the migration of hip pins into the joint in which case the nail was explanted. The complication rates in our study were comparable with the other studies [13][14][15] . (figure 7) Incomplete reduction 4 -------# at distal lock 2 -------Fixed in distraction 2 1 -----1 Incorrect neck screw 2 1 -----1 Implant cutout --4 4 ---1 Delayed union --1 -2 --3 AVN / NU ---1 -2 -2 Difficult distal lock ---4 4 --4 Fixed in varus ----3 -2 3 Screw backout ----1 5 2 2 Metin Uzun et al [16] , in 2009, In a study of 35 patients reported Long-term radiographic complications following treatment of unstable intertrochanteric femoral fractures with the proximal femoral nail and effects on functional results.…”
Section: Discussionsupporting
confidence: 82%
“…Non operative treatment has been found to have a high rate of malunion except in a few studies. Morbidity and mortality associated with conservative treatment, because of prolonged bed ridden state, has been quite high [2] . The last four decades has seen improvement in the management of this common injury, mainly by early surgical fixation and stability of the fracture site.…”
Section: Introductionmentioning
confidence: 99%
“…It acts as a buttress to prevent medialisation of the shaft and provides more efficient load transfer. 13 It is designed to provide linear intraoperative compression of head neck segment to shaft along with rotational stability which minimizes neck malunions resulting in negligible complication rate. 14 It also reduces stress concentration at the tip and the smaller distal diameter may prevent femoral shaft fractures.…”
Section: Discussionmentioning
confidence: 99%